Consumer Loyalty Analysis : Contribution of Commitment and Price - Muammar Rinaldi Amar; Ihdina Gustina; Sesilia Ariska (Enrichment : Journal of Management, 2021)
The purpose of this study was to determine the effect of Commitment and Price on Consumer Loyalty at PT. Almira Nusa Raya in Medan. This type of research data is data with a quantitative approach, research that is processed and analyzed to draw conclusions in the form of numbers. In this study, the sample used was 42 companies. The data analysis technique used multiple regression test by passing the analysis prerequisite test. The results showed that commitment and price simultaneously had a positive and significant effect on consumer loyalty at PT. Almira Nusa Raya. The results of this study are supported by the value of R square (R2), which means that commitment and price have an influence on consumer loyalty at PT. Almira Nusa Raya. While the rest is influenced by other factors originating from outside this research model such as distribution channels, trust, corporate image, customer satisfaction, location, consumer decisions, marketing strategies, consumer perceptions and service quality.